High-value products from ex-situ catalytic pyrolysis of polypropylene waste using iron-based catalysts: the influence of support materials. (December 2021) - Cai, Ning; Xia, Sunwen; Li, Xiaoqiang; Xiao, Haoyu; Chen, Xu; Chen, Yingquan; Bartocci, Pietro; Chen, Hanping; Williams, Paul T.; Yang, Haiping
Highlights: Fe-catalysts with different supports were introduced into waste plastics pyrolysis. Support materials have notably influence on product distribution and properties. Al2 O3 supported catalyst produced more carbon deposits but less gaseous products. Dispersive carbon nanotubes without interwoven were obtained from Fe-SiO2 catalyst. ZSM-5 and TiO2 catalysts resulted in less carbon deposits with irregular morphology. Abstract: Catalytic pyrolysis is considered a promising strategy for the utilisation of plastic waste from the economic and environmental perspectives. As such, the supporting material s play a critical role in the properties of the catalyst. This study clarified this influence on the dispersion of the iron (Fe) within an experimental context. Four different types of typical supports with different physical structures were introduced and explored in a two-stage fixed-bed reactor; these included metallic oxides (Al2 O3, TiO2 ), a non-metallic oxide (SiO2 ), and molecular sieves (ZSM-5). The results show that the liquid products were converted into carbon deposits and lighter gaseous products, such as hydrogen. The Al2 O3 -supported catalyst with a relatively moderate specific surface areas and average pore diameter exhibited improved metal distribution with higher catalytic activity. In comparison, the relatively low specific surface areas of TiO2 and small average pore diameters of ZSM-5 had a negative impact on metal distribution and the subsequent catalytic reformation process; this was because of the inadequate reaction during the catalytic process. The Fe/Al2 O3 catalyst produced a higher yield of carbon deposits (30.2 wt%), including over 65% high-value carbon nanotubes (CNTs) and hydrogen content (58.7 vol%). Additionally, more dispersive and uniform CNTs were obtained from the Fe/SiO2 catalyst. The Fe/TiO2 catalyst promoted the formation of carbon fibre twisted like fried dough twist. Notably, there was interesting correspondence between the size of the reduced Fe nanoparticles and the product distribution. Within certain limits, the smaller Fe particle size facilitates the catalytic activity. The smaller and better dispersed Fe particles over the support materials were observed to be essential for hydrocarbon cracking and the subsequent formation of carbon deposits. The findings from this study may provide specific guidance for the preparation of different forms of carbon materials.